2021
DOI: 10.1177/13591053211009280
|View full text |Cite
|
Sign up to set email alerts
|

National longitudinal evidence for growth in subjective well-being from spiritual beliefs

Abstract: Previous research finds an association between spirituality and subjective well-being. However, the widespread use of poorly defined concepts of spirituality, tautological spirituality scales, and heavy reliance on cross-sectional samples cast doubts on prior findings. Here, we leverage ten waves of panel data from a nationally diverse longitudinal study to systematically test whether having spiritual beliefs leads to growth in personal well-being and life satisfaction ( N = 3257, New Zealand, 2010–2020). Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…In Study 2, we found little evidence to suggest that the R/S identities were associated with subsequent psychological well-being outcomes. These findings generally diverge from previous studies that have either documented a positive ( Nadal et al, 2018 ; Highland et al, 2022 ) or a negative ( King et al, 2013 ; Vittengl, 2018 ; Upenieks and Ford-Robertson, 2022 ) association of spirituality or spiritual self-identification with indicators of psychological well-being. Evidence of null, positive, or negative associations could be due to differences in methodology (e.g., samples, measures, analytic approaches) across studies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In Study 2, we found little evidence to suggest that the R/S identities were associated with subsequent psychological well-being outcomes. These findings generally diverge from previous studies that have either documented a positive ( Nadal et al, 2018 ; Highland et al, 2022 ) or a negative ( King et al, 2013 ; Vittengl, 2018 ; Upenieks and Ford-Robertson, 2022 ) association of spirituality or spiritual self-identification with indicators of psychological well-being. Evidence of null, positive, or negative associations could be due to differences in methodology (e.g., samples, measures, analytic approaches) across studies.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, only a few studies have reported evidence concerning the cross-time associations of R/S identities with subsequent outcomes, with most studies focusing on outcomes within the broad domain of psychological well-being (e.g., Highland et al, 2022 ; Upenieks and Ford-Robertson, 2022 ). In Study 2, we extended the cross-sectional findings of Study 1 to a longitudinal design estimating the effects of the four R/S identities on a wide range of subsequent outcomes across the Big Five personality traits, psychological well-being, generativity, mystical experiences, religious schemata, self-rated religiosity and spirituality, religious centrality, God representation, and cognitive style.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main developmental tasks at the adult stage is the financial aspect, this aspect is considered the responsibility of each individual at the adult development stage (Sorgente & Lanz, 2019). However, in assessing the developmental stages of adult women, it is also necessary to more widely open up various other aspects including SWB and spirituality (Highland et al, 2021). Various studies have shown that spirituality and SWB will provide a different paradigm for the financial concept of adult individuals.…”
Section: Introductionmentioning
confidence: 99%